2017
DOI: 10.1007/978-3-319-66167-4_15
|View full text |Cite
|
Sign up to set email alerts
|

First-Order Interpolation of Non-classical Logics Derived from Propositional Interpolation

Abstract: This paper develops a general methodology to connect propositional and first-order interpolation. In fact, the existence of suitable skolemizations and of Herbrand expansions together with a propositional interpolant suffice to construct a first-order interpolant. This methodology is realized for lattice-based finitely-valued logics, the top element representing true. It is shown that interpolation is decidable for these logics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Let L be a finite set of unary predicate symbols. 1 A model (over L) is a tuple M = (W, ≤, w 0 , A, (P W ) P ∈L ), where (W, ≤) is a quasi-order, the base point w 0 is an element of W such that w 0 ≤ w for all w ∈ W , A is a set, and for each P ∈ L, P W is an order-preserving function from W to P(A), i.e., if w ≤ w ′ in W , then P W (w) ⊆ P W (w ′ ). We will often suppress the superscript W in P W when no confusion can arise.…”
Section: Semanticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Let L be a finite set of unary predicate symbols. 1 A model (over L) is a tuple M = (W, ≤, w 0 , A, (P W ) P ∈L ), where (W, ≤) is a quasi-order, the base point w 0 is an element of W such that w 0 ≤ w for all w ∈ W , A is a set, and for each P ∈ L, P W is an order-preserving function from W to P(A), i.e., if w ≤ w ′ in W , then P W (w) ⊆ P W (w ′ ). We will often suppress the superscript W in P W when no confusion can arise.…”
Section: Semanticsmentioning
confidence: 99%
“…• w, a ∃yϕ, where y ∈ X, if and only if there exists b ∈ A such that w, a ∪ {(y, b)} ϕ; 1 We only need to consider unary predicates in this note.…”
Section: Semanticsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [5] it has been shown that first-order finitely valued logics admit first-order interpolation if they admit propositional interpolation. In this paper we extend these results to the prenex ⊃ prenex fragment of Gödel logic making use of the proof of Lyndon interpolation for propositional Gödel logic from [12].…”
Section: Introductionmentioning
confidence: 99%